Prevalence of Smoking and Related Factors among High School Students in Ahvaz City, Iran - Cheraghi, Maria (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Smoking which is started from adolescence is one of the serious problems of public health and one of the main causes of chronic diseases. The age at smoking onset in developed and developing countries is decreasing; therefore, the best time to perform interventional measures and implement preventive strategies is during or even before adolescence. Therefore, the present study aimed to estimate the prevalence of smoking and related factors among high school students in Ahvaz, Iran. Methods: This was a descriptive analytical study conducted on 900 students randomly selected from high schools of Ahvaz city, Iran, during 2016 and using two-step cluster-randomized sampling method. The relevant data were collected using customized questionnaires. To determine and analyze potential, relationships between smoking and the collected variables, Chi-square, and logistic regression were used in STATA (Windows, version 14). Results: Forty-nine subjects (5.44%) had smoking experience, and most of them were male students showing a significant relationship between smoking and gender (P = 0.009). Moreover, 145 male students (32.2%) stated that the most important factor to start smoking was lack of control by parents over their relationships and 148 female students (33.0%) stated that curiosity was the most effective factor to start smoking. The first smoking experiences based on the different age groups were as follow: 33 students (3.67%) under 10 years old, 41 students (4.56%) between 10 and 14 years old and 50 students (5.56%) over 14 years old. Furthermore, the first smoking experience in both groups was in students over 14 years old. The first people who provided cigarette for students were friends including 61 people (6.78%), grandmother and grandfather including 10 people (1.11%), parents including 4 people (0.44%), and brother or sister including 2 people (0.22%). Moreover, 99 friends (11.0%), 12 parents (1.33%), and a sister or a brother (1.22%) were the first effective factor in smoking. Students’ feeling after smoking included 60 students (6.67%) with a pleasant feeling and 55 students (6.11%) with an unpleasant feeling. Conclusion: A significant relationship was observed between age and smoking, and it can be concluded that the chance to smoke increases with age. According to the critical age of students, school authorities and parents can be effective in preventing most of the abnormal behaviors such as smoking addiction.